Performance Analysis of Single and Multiple Channel FSO System under Turbulent Conditions Using Various Models - Sree Madhuri, A; Venkata Narayana, M; Immadi, Govardhani. (International Journal of Engineering and Technology, 2018)
Telecommunications occupying the major part of research across the world, has become a part and parcel of present day humanâ€™s life. As a part of research many new technologies emerged among which free space optics was found to be highly efficient and a competent technology. So, replacing the present microwave communications, in future free space optics provides many advantages like higher bandwidth, higher data rate (capable of sending up to 1.25 Gbps of data, voice, and video communications simultaneously through the air), low bit error rate and license free long-range communications etc. As a known fact that every coin has two sides, free space optics besides providing the above advantages also suffers from many range limiting factors like fog, beam dispersion, atmospheric absorption, rain attenuation, snow, terrestrial scintillation amongst which rain, scintillation and fog are popular in tropical regions like India. In this paper the effect of rain on FSO link is analysed in 1/1 and 4/4 channel cases and the results were analysed.Â Â